Advances on mechanical designs for assistive ankle-foot orthoses - Lora-Millan, Julio S.; Nabipour, Mahdi; van Asseldonk, Edwin; Bayón, Cristina (Frontiers in Bioengineering and Biotechnology, 2023)
Assistive ankle-foot orthoses (AAFOs) are powerful solutions to assist or rehabilitate gait on humans. Existing AAFO technologies include passive, quasi-passive, and active principles to provide assistance to the users, and their mechanical configuration and control depend on the eventual support they aim for within the gait pattern. In this research we analyze the state-of-theart of AAFO and classify the different approaches into clusters, describing their basis and working principles. Additionally, we reviewed the purpose and experimental validation of the devices, providing the reader with a better view of the technology readiness level. Finally, the reviewed designs, limitations, and future steps in the field are summarized and discussed.